2023
DOI: 10.2478/foli-2023-0037
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Household Incomes of People with Different Levels of Education in Poland and the USA

Kamila Trzcińska,
Elżbieta Zalewska

Abstract: Research background Household income is one of the most important economic categories depending on various factors, in particular on the level of education of the head of the household. Salaries are treated as the market valuation of graduates made by employers. Hence, the question arises of how the education system affects the distribution of household income, in particular in the group of people with higher education. Purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The research conducted by the World Bank demonstrates a positive correlation between the level of education and entrepreneurial activities. The analysis has demonstrated that the higher the level of education, the better the financial situation of the household (Trzcińska & Zalewska, 2023). Therefore, it is possible to increase the income level of poor households by improving their access to education (Hung Van Vu, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research conducted by the World Bank demonstrates a positive correlation between the level of education and entrepreneurial activities. The analysis has demonstrated that the higher the level of education, the better the financial situation of the household (Trzcińska & Zalewska, 2023). Therefore, it is possible to increase the income level of poor households by improving their access to education (Hung Van Vu, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%